2019
DOI: 10.1039/c8nj05815f
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between copper and different metal oxides in the selective hydrogenolysis of glucose

Abstract: The coordination of copper and different acid/basic sites could promote the selective hydrogenolysis of glucose to polyols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…For instance, Choudhary reported that the proper B/L ratio favors xylulose dehydration to furfural at low reaction temperatures; [ 27‐28 ] Liu et al . reported that the presence of Lewis acid sites and hydrogenation sites on a Cu/γ‐Al 2 O 3 catalyst had high glycol selectivity (66.6%) for glucose conversion at high reaction temperatures, [ 76 ] and the results were also in agreement with those reports. [ 77‐79 ]…”
Section: Resultssupporting
confidence: 88%
“…For instance, Choudhary reported that the proper B/L ratio favors xylulose dehydration to furfural at low reaction temperatures; [ 27‐28 ] Liu et al . reported that the presence of Lewis acid sites and hydrogenation sites on a Cu/γ‐Al 2 O 3 catalyst had high glycol selectivity (66.6%) for glucose conversion at high reaction temperatures, [ 76 ] and the results were also in agreement with those reports. [ 77‐79 ]…”
Section: Resultssupporting
confidence: 88%
“…However, the yields of the identified products did not increase appreciably. The obtained data evidenced high conversion and carbon loss at temperatures above 200 °C due to changes in the reaction pathways; at high temperatures, glucose was converted into both insoluble humins and soluble polymeric byproducts [51]. This could be attributed to the oligomerization reaction of both glucoses, HMF and other reaction products (fructose, other C4-C5 sugars).…”
Section: Catalytic Testmentioning
confidence: 91%
“… 21 A Cu/γ-Al 2 O 3 catalyst can promote C–C and C–O bonds cleavage, leading to the conversion of glucose to glycols (with a selectivity of 67%). 22 Ordered mesoporous 10.9% Ni/6.3% CeO 2 –Al 2 O 3 showed better catalytic performance in the hydrogenolysis of sorbitol, obtaining a 56.9% yield of ethylene glycol (EG) and 1,2-PG. 23 A Cu–Ni/ZrO 2 catalyst was efficient for xylitol conversion to EG and 1,2-PG with a 65% total selectivity in water without a base additive.…”
Section: Introductionmentioning
confidence: 99%